Papers of Miles Franklin - Franklin, Miles, 1879-1954. (1877)
(1) An album containing Christmas and New Year cards. (2) 3 folders of typewritten drafts of stories by "Brent of Bin Bin". (3) Album containing postcards, some overseas, some of Australian country towns, especially Tumut, some Lampe family photographs.
Manuscript reference no. : MS 477.
Guide to collections of manuscripts relating to Australia
Stella Maria Sarah Miles Franklin was born on 14 October 1879 at Talbingo, N.S.W. My Brilliant Career, her first novel, was published in 1901. For many years she lived in the U.S.A. and then in England. She returned to Australia permanently in 1933. She wrote many works under the pseudonym of "Brent of Bin Bin". A satire, Pioneers on Parade (1939), was written in collaboration with Dymphna Cusack, and a literary biography, Joseph Furphy, the Legend of a Man and his Book (1944), was written with Kate Baker.
Descriptive list (3 p.) available.
Keywords: Franklin, Miles, -- 1879-1954 -- Archives; Lampe family -- Portraits; Authors, Australian -- Portraits; Australian literature; Authors